Community Diversity and Unity in Witihama, Adonara - Robert H. Barnes (Antropologi Indonesia, 2004)
For fourteen months in 2000-2001, I conducted a research in the District of Witihama, eastern Adonara. Witihama is a religiously mixed community, made up of Muslims and Catholics. However, both groups also practice blood sacrifice and carry out ceremonies required by adat. Muslims and Catholics are closely related by ties of marriage and descent. In the recent historical past, as well as in the ancient legendary past, the community has a remembered history of bloody warfare and murder, not linked to questions of modern religious allegiances, which provide incentives to take precautions to maintain community harmony and peace. Mindful of sectarian conflict elsewhere in Indonesia, Catholics and Muslims maintain close ties of cooperation and solidarity. On holidays like Christmas, Easter and Idul Fitri, for example, they hold community meetings to express mutual friendship. Members of the District have suffered from conflict elsewhere in Indonesia, for example during the fighting between Suku Batak and the 'Flores people' in 1999 in Batam, in the Moluccas and in the violence inDili, East Timor. Refugees from these other conflicts came and went while I was there. There have been attempts at sectarian provocation in Witihama by people from elsewhere in the past, leading to their expulsion. There was an unexplained incident in which a hand grenade exploded in Witihama killing one child and injuring two others, causing considerable consternation within the community. Rumors of plans to bomb the Catholic Church were taken seriously. Efforts to place East Timorese refugees in the Kabupaten of Flores Timur were strongly resisted on grounds of safety and local peace. Finally the national move toward regional autonomy led to Witihama becoming a separate Kecamatan and resulted in moves to turn Flores and Lembata into a separate Province.